A framework for telepsychiatric training and e-health: Competency-based education, evaluation and implications. (2nd November 2015) - Hilty, Donald M.; Crawford, Allison; Teshima, John; Chan, Steven; Sunderji, Nadiya; Yellowlees, Peter M.; Kramer, Greg; O'neill, Patrick; Fore, Chris; Luo, John; Li, Su-Ting
Abstract: Telepsychiatry (TP; video; synchronous) is effective, well received and a standard way to practice. Best practices in TP education, but not its desired outcomes, have been published. This paper proposes competencies for trainees and clinicians, with TP situated within the broader landscape of e-mental health (e-MH) care. TP competencies are organized using the US Accreditation Council of Graduate Medical Education framework, with input from the CanMEDS framework. Teaching and assessment methods are aligned with target competencies, learning contexts, and evaluation options. Case examples help to apply concepts to clinical and institutional contexts. Competencies can be identified, measured and evaluated. Novice or advanced beginner, competent/proficient, and expert levels were outlined. Andragogical (i.e. pedagogical) methods are used in clinical care, seminar, and other educational contexts. Cross-sectional and longitudinal evaluation using quantitative and qualitative measures promotes skills development via iterative feedback from patients, trainees, and faculty staff. TP and e-MH care significantly overlap, such that institutional leaders may use a common approach for change management and an e-platform to prioritize resources. TP training and assessment methods need to be implemented and evaluated. Institutional approaches to patient care, education, faculty development, and funding also need to be studied.